Application of salt extracted peanut seeds in the pretreatment of palm oil mill effluent (POME) - Birima A.H.; Ahmed A.T.; Noor M.J.M.M.; Sidek L.M.; Muda Z.C.; Wong L.S. (Bellwether Publishing, Ltd., 2023)
chemical oxygen demand; coagulation; effluent; sodium chloride; turbidity; waste treatment; Arachis hypogaea